2015
DOI: 10.5334/ijic.2244
|View full text |Cite
|
Sign up to set email alerts
|

The Norrtaelje model: a unique model for integrated health and social care in Sweden

Abstract: Many countries organise and fund health and social care separately. The Norrtaelje model is a Swedish initiative that transformed the funding and organisation of health and social care in order to better integrate care for older people with complex needs. In Norrtaelje model, this transformation made it possible to bringing the team together, to transfer responsibility to different providers, to use care coordinators, and to develop integrated pathways and plans around transitions in and out of hospital and fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
81
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(93 citation statements)
references
References 3 publications
9
81
3
Order By: Relevance
“…Regarding its impact at community level, multimorbidity shows positive correlations with number of outpatient visits [7], polypharmacy [8] and with patients' frailty [9]. The latter being a strong modulator of the need for both homecare and social support services [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding its impact at community level, multimorbidity shows positive correlations with number of outpatient visits [7], polypharmacy [8] and with patients' frailty [9]. The latter being a strong modulator of the need for both homecare and social support services [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…People who consider themselves in need of seeing a medical doctor seem to seek care at the emergency departments rather than primary care clinics where, depending on their health problems, they may be seen by a nurse. Local initiatives have, however, shown that developing and implementing integrated care between hospitals, primary care and social care reduces the number of hospital admissions and readmissions [6869]. For example, at a primary care clinic in Borgholm, a municipality in the south of Sweden with the oldest population in the country, dramatic changes have been made to improve access to healthcare.…”
Section: Discussionmentioning
confidence: 99%
“…Other high bed number countries include Austria (intercept 1350) and Germany (1320), hence while the average for developed countries is a helpful benchmark it is important to realize that countries with high levels of integrated care such as Sweden (intercept 800), Singapore and New Zealand (790) operate with around 40% fewer beds that the developed countries average (Figure ). However, such levels of bed provision are only achieved after many years of effort enabled by government policy . Australia is generally not considered to have a highly integrated health care service, and hence bed provision lies near to the International average for developed countries.…”
Section: Discussionmentioning
confidence: 99%